Modelo híbrido de aprendizagem no ensino de língua portuguesa: estudo de caso no ensino médio - Silva, Maria Izabel Oliveira Da [UNIFESP] (2019)
This research is located in the field of Public School, Teacher Training and Pedagogical Practices. This is an educational case study, under the qualitative methodological approach of a descriptive nature, related to the implementation of blended learning in the Portuguese language subject for high school students of the second year of right school located in the south zone of the city of São Paulo. In order to do so, the student's mobile phone (smartphone) was used as a pedagogical tool anchored in active methodologies, and the use of the web tools Google Classroom and Kahoot focused on education and Google Forms focused on the search or collection of online. The general objective is to investigate the extent to which the implementation of blended learning favors the conceptual learning of the Portuguese language, as well as its impact on the behavior of high school students in relation to the performance both in the activities proposed in the classroom and in the online activities. In this sense, didactic sequences were applied during the 2018 school year using the flipped classroom with the Google Classroom and Google Forms applications, and the model rotation by stations using the Youtube video sharing platform and the Google search site. In addition, classroom literature tournaments were conducted using Kahoot software. As data collection instruments, two questionnaires were applied to students in the second year of high school, the first being before, and secondly, after the implementation of blended learning, in addition to a semi structured exploratory interview subsidizing the analysis of student learning, as well as their perception of this new teaching approach. The students' responses indicated that the experience with hybrid teaching was successful both from the conceptual point of view of learning the Portuguese language and behavioral in terms of their willingness and autonomy to learn.